Le moi colonisé - El Khayat, Rita (TransCulturale, 2024)
In this presentation, the author of the book « Lo schiaffo » (Slap in the face) has tempted do describe the phenomenon of colonization through all its faces, its periods, its meanings. It’s obviously very complex and impossible to describe in a unique book; but, this one is the long memory of humiliation and the expression of an enormous suffering of a girl abused by a teacher, suffering burning until now in the heart of the author. The slap in the face of the girl that was an unfair act, something impossible to forgive, to forget or to say before decades. It was impossible to publish this book in France and the Italian edition gave this kind of reparation and consolation to the woman that never was able to say the event to someone. Adult and aware of the importance of testimonies, revelations and analysis, she found the courage to, at last, write it and explain all the circumstances of all that, rooted in colonization and the despise of the Other, when he’s submitted, defeated and half destroyed by the aleas of History.